2018
DOI: 10.1111/acps.12960
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in adult and adolescent patients with schizophrenia: combined analysis of nine RCTs

Abstract: These findings are informative to identify potential placebo responders at the earliest opportunity for optimal trial design for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…If evidence existed of an enhanced placebo response over time, as has been suggested repeatedly in the past years, this response would have been apparent in both the control and the treatment groups because of randomization and thus would have canceled out. Furthermore, the concept of placebo response, although regularly investigated, cannot be studied by looking at the observed responses in control groups, for the same reasons that this approach does not work for the treatment groups, as this study has shown.…”
Section: Discussionmentioning
confidence: 96%
“…If evidence existed of an enhanced placebo response over time, as has been suggested repeatedly in the past years, this response would have been apparent in both the control and the treatment groups because of randomization and thus would have canceled out. Furthermore, the concept of placebo response, although regularly investigated, cannot be studied by looking at the observed responses in control groups, for the same reasons that this approach does not work for the treatment groups, as this study has shown.…”
Section: Discussionmentioning
confidence: 96%
“…Attempts to identify clinical trial factors responsible for high placebo response have been many and the study of Kubo et al. in this issue of Acta describes some important insights into this problem seen in antipsychotic trials. They report that a clinical feature of the schizophrenia population studied (i.e., disorganized thought scores) as well as lower PANSS (positive and negative syndrome scale) total score reduction at week 1 were associated with higher placebo response.…”
Section: How Can We Fix the Problem?mentioning
confidence: 99%
“…Innovative solutions are needed such as the possibility of a paradigm shift from the randomized placebo‐controlled design with classical statistics and ‘purified’ patients to consideration of other designs such as including real‐world complicated patients and making comparisons of new agent augmentation to treatment as usual rather than to placebo; open‐label treatment of new agents with randomization only of responders to double blind continuation or discontinuation of treatment; or here is a shocker: experimenting with statistics that would allow fair evaluation of drug versus placebo by making some adjustments AFTER randomization, such as those suggested by Kubo et al. , namely by dropping out early responders. A variation on this is already suggested by the novel Sequential Parallel design now being more commonly implemented in modern trials with novel statistics where the placebo non‐responders are re‐randomized to drug or placebo and the placebo responders are dropped out .…”
Section: How Can We Fix the Problem?mentioning
confidence: 99%
“… 31 Second, as with other randomized, placebo-controlled clinical trials in schizophrenia, the placebo effect bias could have had an impact on the results. 57 However, such a placebo effect would have created a conservative bias minimizing potential differences between Risperidone ISM and placebo. Third, higher adherence rates, which are common among patients enrolled in clinical trials, as well as the highly select clinical trial population, may be different from what is observed in real-world settings.…”
Section: Discussionmentioning
confidence: 99%